SEGMENTASI PASAR WISATAWAN MANCANEGARA DI DKI JAKARTA - Rina Ayu Vildayanti (JABE (Journal of Applied Business and Economic), 2016)
Indonesia tourism potential is high enough. Jakarta is one of the destinations that have considerable tourism potential in Indonesia. Jakarta tourism development requires a serious governance. The successful development of Jakarta into an international tourist resort depends on the seriousness of the government to maximize the management of tourism in the city of Jakarta. This study aims to describe descriptively, the foreign tourist market segmentation in Jakarta based on length of stay, the amount of expenditure and the type of accommodation (hotel). Qualitative methods using secondary data related to length of stay, the amount of expenditure and the type of accommodation (hotel) used for foreign tourists visiting Jakarta. Expected results of the study could  be the rationale in establishing the Jakarta tourism more broadly.